Figure of the acousmatic voice - Bénard, Julie (2022)
This article focuses on prosopopoeia as a “figure of the voice” in Samuel Beckett’s play for television What Where(1986/2013) and as it is defined by Bruno Clément. Prosopopoeia is a figure and a voice: both take part in the thought process. They allow the subject to think the thought process through self-hearing. Prosopopoeia is thus reflexive and participates in the phenomena of the mind which are carried out by the voice of the self, whose externalization gives way to an inner dialogue of sorts which is exposed to otherness. I will study this principle which is at the very heart of Beckett’s play along with the status of the voice. By being carried out by a figure of thought – prosopopoeia – the voice questions its origin through similarity and dissimilarity which highlights its equivocal nature. Indeed, if prosopopoeia is a figure that gives a voice to what has no existence, I will show that this voice is necessarily acousmatic.